Ritual and the Constitution of Social Structure - Pertierra, Raul (The Australian journal of anthropology, 1987)
The constitution and reproduction of structure through the action orientations of social actors remains a basic question in the social sciences. Most sociological theories have stressed a purposive-rational model of action in the constitution of structure. These models of action have not been able to account for either the external constraints of structure or for its internal obligatory nature. This paper argues that a theory of ritual action is able to explain both the external and the internal obligatory nature of social structure.